2022
DOI: 10.1038/s41390-022-02362-8
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of an exercise program in children with inflammatory bowel disease in remission

Abstract: Background The aim of our study was to investigate the impact of a structured exercise program on bone mineral density (BMD) and body composition parameters in children and adolescents with IBD in remission. Methods Patients were recruited to participate in a 6-month exercise program. Total body less head (TLBH) dual energy X-ray absorptiometry (DXA) was used to measure BMD. The same method was used to assess fat mass (FM) and lean body mass (LBM) at baseline and at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Two studies focused on pediatric patients with IBD, and both demonstrated beneficial effects of their intervention on HRPF components[ 53 , 54 ]. Mählmann et al [ 53 ] demonstrated that an 8-wk aerobic exercise training intervention with active video gameplay increased the distance reached on the 6-min walk test, a practical field test for assessing cardiorespiratory fitness, in children with IBD in remission and with active disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies focused on pediatric patients with IBD, and both demonstrated beneficial effects of their intervention on HRPF components[ 53 , 54 ]. Mählmann et al [ 53 ] demonstrated that an 8-wk aerobic exercise training intervention with active video gameplay increased the distance reached on the 6-min walk test, a practical field test for assessing cardiorespiratory fitness, in children with IBD in remission and with active disease.…”
Section: Resultsmentioning
confidence: 99%
“…Mählmann et al [ 53 ] demonstrated that an 8-wk aerobic exercise training intervention with active video gameplay increased the distance reached on the 6-min walk test, a practical field test for assessing cardiorespiratory fitness, in children with IBD in remission and with active disease. The effects of a home-based resistance exercise training program for 6 mo on HRPF components in children and adolescents with IBD in remission were investigated by Trivić et al [ 54 ]. Lean body mass significantly improved, whereas lean body mass age-based and sex-based z-scores did not.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, we did not find a significant correlation between PA and CRP. On the contrary, Trivić et al reported that a 6‐month home‐based structured exercise programme improved lean body mass 31 . However, vigorous PA may cause gut dysbiosis, 22 which may also be negative for IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…As previously noted, malnutrition is one of the symptoms of CD in children. Moreover, in our previous study, in which we evaluated the body composition of CD patients who were in clinical remission, we showed reduced lean body mass using DXA [20]. There are a limited number of pediatric studies that evaluated muscle mass in children with CD [7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 94%